EUV emission spectra from excited Ar, Xe and Sn ions produced in capillary discharges - Nowakowska-Langier, K.; Jakubowski, L.; Baronova, E.O.; Czaus, K.; Rabinski, M.; Mirowski, R.; Jakubowski, M.J.; Wiraszka, A. (Вопросы атомной науки и техники, 2008)
This work presents preliminary results of an extreme ultraviolet emission obserwations of a capillary discharge plasma. The main purpose of measurements was to demonstrate the spectral range covered by the system working parameters. The spectroscopic studies were carried out by means of an XEUV spectrometer in the Johann geometry. The results provide general information about the radiation processes from the xenon, argon and tin plasma in the range from 12 to 63 nm. Представлено перші результати спостереження емісії вакуумного ультрафіолетового (ВУФ) випромінювання в плазмі капілярного розряду. Основною метою вимірів була демонстрація покриття спектрального діапазону робочими параметрами системи. Спектроскопічні дослідження проведені за допомогою ВУФ спектрометра Джоханнівської геометрії. Результати подають загальну інформацію про процеси випромінювання з ксенонової, аргонової і свинцевої плазми в діапазоні від 12 до 63 нм. Представлены первые результаты наблюдения эмиссии вакуумного ультрафиолетового (ВУФ) излучения в плазме капиллярного разряда. Основной целью измерений являлась демонстрация покрытия спектрального диапазона рабочими параметрами системы. Спектроскопические исследования проведены с помощью ВУФ спектрометра Джоханновской геометрии. Результаты дают общую информацию о процессах излучения из ксеноновой, аргоновой и свинцовой плазмы в диапазоне от 12 до 63 нм.